If it's not what You are looking for type in the equation solver your own equation and let us solve it.
65=-13(x+13)
We move all terms to the left:
65-(-13(x+13))=0
We calculate terms in parentheses: -(-13(x+13)), so:We get rid of parentheses
-13(x+13)
We multiply parentheses
-13x-169
Back to the equation:
-(-13x-169)
13x+169+65=0
We add all the numbers together, and all the variables
13x+234=0
We move all terms containing x to the left, all other terms to the right
13x=-234
x=-234/13
x=-18
| y=1.5+ | | 15x-35+55=180 | | 2x-10=4x-80 | | 3(x)+25=46 | | 10(x+30)=-40 | | y-35=36 | | 4n-26=59 | | c-59=13 | | c-69=13 | | 180-y-y=18 | | x3=85 | | 50-a/11=48 | | 3(4x+5)=57 | | 42=429b | | 3x+45+2x=180 | | -7x=30=58 | | 12x+8=10x+2 | | 10x+2=12x+8 | | 10x+2=12x8 | | m+(m-10)+(m+10)=180 | | -4-3r=2 | | 5(x-1)-2(5x+2)=2(4x-9)+x+2 | | 6.6=11x/15 | | 4x+31=5x-14 | | -5.6a=-12.88 | | 16x=64^x+4 | | 4000/x=1.5 | | (1)/(6)x=7 | | 4n-(4)=-52 | | 2x+29=3x-4 | | 21+8a=93.8 | | 143=3x+22 |